Overcoming educational silos: a mixed-methods framework for Curriculum Ideological-Political Education in China - Wei, Wanqing; Yang, Xin (Frontiers in Education, 2026)
IntroductionThe phenomenon of “educational silos”–the structural fragmentation between professional training and values education–remains a persistent challenge in global higher education. While China’s Curriculum Ideological–Political Education (CIPE) policy offers a systemic response to this issue, existing research often lacks a robust theoretical framework to explain the mechanisms of integration.MethodsThis study addresses this gap by developing a dialectical integration framework through a mixed-methods design, combining a cross-linguistic bibliometric analysis of 851 publications (2014–2024) with multi-site case studies across 12 universities.ResultsThe analyses identify three distinct integration modalities—complementary, dialogical, and transformative—which function as context–dependent strategies rather than hierarchical stages. Furthermore, a meta-analytical synthesis indicates a moderate positive association between these initiatives and knowledge consolidation, although effects diminish in behavioral domains.DiscussionOvercoming educational silos appears to require dialectical negotiation of disciplinary boundaries and explicit alignment between professional competencies and value-oriented goals. The proposed framework offers a transferable typology to support curriculum design, institutional implementation, and evaluation of integration quality.